Periprocedural Pericardial Effusion Complicating Transcatheter Left Atrial Appendage Occlusion: A Report From the NCDR LAAO Registry. (2nd April 2022) - Price, Matthew J.; Valderrábano, Miguel; Zimmerman, Sarah; Friedman, Daniel J.; Kar, Saibal; Curtis, Jeptha P.; Masoudi, Frederick A.; Freeman, James V.
Abstract : Background: Pericardial effusion (PE) is a potential complication of transcatheter left atrial appendage occlusion. The objective of this study was to investigate the incidence, associated characteristics, and outcomes of PE following left atrial appendage occlusion. Methods: Patients in the NCDR LAAO Registry who underwent a Watchman procedure between January 1, 2016 and December 31, 2019 were included. The primary outcome was in-hospital PE requiring intervention (percutaneous drainage or surgery). Odds ratios (ORs) were calculated for adverse event rates associated with PE. Results: The study population consisted of 65 355 patients. The mean patient age was 76.2±8.1 years, and the mean CHA2 DS2 -VASc score was 4.6±1.5. PE occurred in 881 patients (1.35%). Clinical variables independently associated with PE included older age, female sex, left ventricular function, paroxysmal atrial fibrillation, prior bleeding, lower serum albumin, and preprocedural dual antiplatelet therapy; procedural variables included number of delivery sheaths used, sinus rhythm during the procedure, and moderate sedation rather than general anesthesia. PE was associated with increased risk of in-hospital stroke (OR, 6.58 [95% CI, 3.32–13.06]; P <0.0001), death (OR, 56.88 [95% CI, 39.79–81.32]; P <0.0001), and the composite of death, stroke, or systemic embolism (OR, 28.64 [95% CI, 21.24–38.61]; P <0.0001). PE during the index hospitalization was associated with increased risk of death (OR, 3.52 [95% CI, 2.23–5.54]; P <0.0001) and the composite of death, stroke, or systemic embolism (OR, 3.42 [95% CI, 2.31–5.07]; P <0.0001) between discharge and 45-day follow-up. Conclusions: In-hospital PE during transcatheter left atrial appendage occlusion is infrequent but associated with a substantially higher risk of adverse events, including in-hospital and early postdischarge mortality. Strategies to minimize PE are critical to improve the risk-benefit ratio for this therapy.